The Influence of School Shooting on Victim as Seen in American Movie “The Fallout” 2022 - Meutia Nurul Izzah; Nizam Ahsani (CV. Creative Tugu Pena, 2024)
America is known as a country that emphasises freedom for its people. However, America has the highest crime rate in the world. Mass shootings are among the crimes that pose a major concern. This study aims to present the impacts of school shootings on victims, as well as the role of families and counselors in assisting the healing process of PTSD victims as depicted in the movie The Fallout (2022). The study employs a qualitative approach, utilizing primary data such as scenes, dialogues, and body language from the movie. The data collection method involves understanding the movie and sorting the data based on the study's objective. To analyze the main data, this research used two main theories, namely the PTSD theory by Freud (1917) and Symbolic Interactionism by Blumer (1986), and strengthened it by using additional data from scientific journals. This research concludes that victims of PTSD resulting from school shootings encounter various psychological symptoms, including alterations in their characteristics, avoidance of the tragedy, and the occurrence of nightmares. Through the process, family and counselors act as parties who can provide action and create a safe space for PTSD victims to heal.